Technology integration in higher education : social and organizational aspects - Surry, Daniel W., 1962-; Stefurak, James R., 1974-; Gray, Robert M., 1965- (Hershey, PA : Information Science Reference, 2011)
"This book provides a sound overview of the ways that technology influences the human and organizational aspects of higher education and how technology is changing the relationship between faculty and students, higher education experience, and the role of colleges and universities within society as a whole"-- Provided by publisher.
Includes bibliographical references p. 343-385 and index.
Keywords: Education, Higher -- Computer-assisted instruction; Education, Higher -- Effect of technological innovations on; Educational technology -- Social aspects